2009
DOI: 10.1017/s1049096509090787
|View full text |Cite
|
Sign up to set email alerts
|

Internet Voting in Comparative Perspective: The Case of Estonia

Abstract: Several countries have conducted Internet voting trials in binding public elections over the past decade, including Switzerland, the United Kingdom, and the United States. However, Estonia—a former Soviet republic and now a full member of the European Union—has advanced the farthest in deploying Internet voting. In this article, we focus on how the Estonians have systematically addressed the legal and technical considerations required to make Internet voting a functioning voting platform, as well as the politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 25 publications
1
85
1
2
Order By: Relevance
“…For increasing reliability of the system Dimitris [8] suggest to decrypt and count votes from ballots only after proper auditing procedures are followed. Also voting control and recount should be feasible by system while anonymity of voters is maintained [9] [10].…”
Section: Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…For increasing reliability of the system Dimitris [8] suggest to decrypt and count votes from ballots only after proper auditing procedures are followed. Also voting control and recount should be feasible by system while anonymity of voters is maintained [9] [10].…”
Section: Reliabilitymentioning
confidence: 99%
“…To prevent malicious users from using data even when they have access to it, data should be encrypted when stored. To increase security data as well as keys, identifiers and metadata are also encrypted [7] [8]. Also communication between systems located remotely need to be encrypted to prevent malicious users from eavesdropping.…”
Section: Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Estonia was a victim of a major cyber-attack in 2007 immediately after the national elections, which sensitized the country for matters of e-vulnerability [18]. After intensive research by [6)], they identified four important reasons for the success of e-voting in Estonia including: …”
Section: Estonia's E-voting Experiencementioning
confidence: 99%
“…This at times leads to political unrest [1]. Many researchers suggested e-voting as a solution to the problems of paper ballots electoral process [2][3] [4][5] [6][7] [8].…”
Section: Introductionmentioning
confidence: 99%